INFLUENCE OF PARENTAL SOCIO ECONOMIC STATUS ON CARIES PREVALENCE AMONG CHILDREN USING PUFA INDEX - Pasha, Lubna; Farid, Huma; Hassan, Faiza; Pasha, Yasir (Pakistan Oral & Dental Journal, 2018)
Dental caries and the resulting pulpitis is a reality of modern day life style. Important determinant for dental caries progression may be socioeconomic status (SES), gender, race, oral hygiene and habits like tobacco consumption. An association of dental caries with SES is still questionable. The objectives this study are to access the prevalence of untreated dental caries using PUFA index among 12 to 14 years old school going children and to determine an association of PUFA index with the socio-economic status (SES) of parents. A cross sectional study of three months duration was conducted among 12 -14 years old school going children reporting at the Operative Dentistry department of Margalla institute of Health Sciences Rawalpindi. An assessment of teeth and adjacent soft tissues of 300 children was carried out with mouth mirror. PUFA score of the whole sample was 1.42. The "P" component formed the majority of PUFA score (80%). Children with poor SES had a mean PUFA score of 1.32 while children with middle class SES had a mean PUFA score of 1.48. A statistically significant association was seen between SES and P component of PUFA (p?0.001). These results with high degree of pulpal involvement in children belonging to middle class SES highlight the fact that there is a need for educating both parents and children regarding deleterious effects of refined sugars on oral health.
Keywords: Untreated Dental caries; PUFA index; Pulpal involvement; Permanent dentition